2022
DOI: 10.3390/ani12121507
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Enteropathy in Dogs—Epidemiologic Aspects and Clinical Characteristics of Dogs Presenting at Two Swedish Animal Hospitals

Abstract: Information about prevalence and breed predisposition of canine chronic enteropathy (CE) is limited. The aim of this retrospective study was to investigate period prevalence, breed disposition, clinical features, diagnostic results, and treatment response of CE in dogs presenting at two Swedish animal hospitals during 2013–2018. A medical record search was performed to identify CE dogs including those with ≥3 visits because of gastrointestinal disease and/or that had undergone gastroduodenoscopy/colonoscopy du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 58 publications
2
11
0
Order By: Relevance
“…useful in predicting response to EL. The Rs had a median CCECAI of 6.5(3)(4)(5)(6)(7)(8) and age of 2.75 (0.9-11) years, which are consistent with publications reporting a wide range of ages and disease severity in diet-responsive CE dogs 12,48,49. Our results conflict with previous reports finding diet-responsive CE dogs to be younger, with lower clinical activity indices, as compared to dogs not responding to diet 1,6.…”
supporting
confidence: 79%
See 2 more Smart Citations
“…useful in predicting response to EL. The Rs had a median CCECAI of 6.5(3)(4)(5)(6)(7)(8) and age of 2.75 (0.9-11) years, which are consistent with publications reporting a wide range of ages and disease severity in diet-responsive CE dogs 12,48,49. Our results conflict with previous reports finding diet-responsive CE dogs to be younger, with lower clinical activity indices, as compared to dogs not responding to diet 1,6.…”
supporting
confidence: 79%
“…Dietary therapy is a mainstay of CE management in dogs, with resolution of clinical signs reported in up to 69% of dogs after dietary intervention. [1][2][3][4] Treatment success has been documented with hydrolyzed protein, limited ingredient, and fat-restricted diets. 3,5 The mechanisms underlying clinical improvement after diet change are incompletely understood, but likely involve host, microbiome, and dietary factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a practical perspective, our findings support the strategy of conducting multiple dietary trials in dogs with CE, with or without PLE, before escalating to use of antimicrobial or immunosuppressive agents 5,7,16 . We speculate that the high proportions of dogs with immunosuppression‐responsive versus food‐responsive enteropathy reported in some studies may reflect therapeutic escalation based on a single dietary trial 40,41 …”
Section: Discussionsupporting
confidence: 55%
“…5,7,16 We speculate that the high proportions of dogs with immunosuppression-responsive versus foodresponsive enteropathy reported in some studies may reflect therapeutic escalation based on a single dietary trial. 40,41 In dogs with PLE, the role of diet as monotherapy is less clear because the prognosis is poor and such dogs often receive concurrent medications or refuse to eat therapeutic diets. [3][4][5]7,10,12,16,18 We showed that diets containing hydrolyzed proteins and moderate amounts of fat (3.97 g fat /100 kcal) support an increase in body weight, serum albumin concentration, and sustained remission.…”
Section: Discussionmentioning
confidence: 99%